Faults in Modular Multilevel Cascade Converters—Part I: Reliability, Failure Mechanisms, and Fault Impact Analysis - Felix Rojas; Cristobal Jerez; Christoph Michael Hackl; Oliver Kalmbach; Javier Pereda; Jonathan Lillo (IEEE Open Journal of the Industrial Electronics Society, 2022)
Modular multilevel cascade converters (MMCCs) are considered a promising power electronics topology in industry. Their scalability allows to reach (ultra/very) high voltage levels with low harmonic content and high efficiency and makes MMCCs an ideal solution for high-power applications, such as electrical drives, solid-state transformers, and high-voltage direct-current (HVdc) transmission systems. However, the high levels of thermal, electrical, and mechanical stress on the power electronics devices and the large number of components (e.g., capacitors or semiconductors) make MMCCs prone to faults reducing its reliability. In this first part of the article, a comprehensive overview of the reliability of MMCCs, failure mechanisms, and fault impact analysis in MMCCs, including failure rates and fault modes is presented. Also, a set of tables that collect all information to easily detect and identify faults in MMCCs is presented.